1999
DOI: 10.1136/emj.16.5.322
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of retrospective triage decisions as a standardised instrument for audit.

Abstract: Objectives-To determine the level of agreement between senior medical staff when asked to perform retrospective case note review of nursing triage decisions, both before and after development of a consensus approach. Methods-Four medical reviewers independently allocated triage categories to 50 emergency department patients after review oftheir case notes. They were blind to the identity of the triage nurse and their triage categorisation. The process was repeated twice, firstly after agreement on a consensus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 7 publications
1
26
0
4
Order By: Relevance
“…As Goodacre, Gillet, Harris, et al (1999) identified, when they performed a retrospective audit of nursing triage decisions using the NTS, there was only fair to moderate consistency between physician reviewers auditing triage decisions. Equally, as Brillman, Doezema, Tanberg, et al (1996) states, verifiable gold standards for triage do not exist.…”
Section: Simultaneous Parallel Codingmentioning
confidence: 99%
See 2 more Smart Citations
“…As Goodacre, Gillet, Harris, et al (1999) identified, when they performed a retrospective audit of nursing triage decisions using the NTS, there was only fair to moderate consistency between physician reviewers auditing triage decisions. Equally, as Brillman, Doezema, Tanberg, et al (1996) states, verifiable gold standards for triage do not exist.…”
Section: Simultaneous Parallel Codingmentioning
confidence: 99%
“…Patients with more than one presenting complaint may be triaged by more than one algorithm, each leading to a different category (Goodacre, Gillet, Harris, et al 1999). The TATTT is universally applied to all adult injury based presentations regardless of the aetiology of the patients presenting complaint.…”
Section: Algorithms and Triagementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore these decisions can have a profound effect on the health outcomes of the patient (Considine et al, 2000). Failure to categorise patients appropriately may result in these patients receiving medical attention that is unacceptably delayed or unnecessarily expedited Bucknall, 2001 andGoodacre, 1999). This situation has implications for both the patient being triaged and the ability of the ED to function effectively.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the triage nurse must rely upon general guidelines to assess urgency and prioritize care, and many triage decisions are based primarily on the nurse's own clinical experience. While the validity of the general triage process has recently been studied, [15][16][17][18][19][20][21][22][23][24] little is known about the ED triage of HIV-infected patients.…”
mentioning
confidence: 99%